Comprehensive analysis of cuproptosis-related genes in diabetic cardiomyopathy - Jun Li; Hua Zhang; Xinyue Duan; Meina Zhang; Xin Li; Chunyan Hao (PLoS ONE, 2025)
Background Diabetic cardiomyopathy (DCM) represents a distinct myocardial pathology arising from chronic diabetic metabolic disturbances, characterized by progressive structural and functional abnormalities that frequently culminate in heart failure. Cuproptosis, a novel form of cell death, is highly linked to mitochondrial metabolism and mediated by protein lipoylation. However, studies are limited on the clinical significance of cuproptosis-related genes (CRGs) in DCM. Therefore, it is helpful to identify CRGs involved in DCM and explore their expression and molecular mechanisms. Methods We downloaded three datasets of DCM from the GEO database and a set of cuproptosis-related genes with 176 genes. Following the identification of the differentially expressed cuproptosis-related genes(DECRGs) and hub genes, we performed the functional annotation, protein-protein interaction network, co-expression network analysis, mRNA-miRNA regulatory network.The GSE5606 dataset was then used to verify hub genes. Finally, we validated the expression of hub genes in a high glucose-induced H9C2 cell injury model via RT-qPCR. Results We identified 14 DEFRGs and 7 key genes in the DCM samples compared to the control. Functional enrichment analysis revealed that DECRGs are associated with several pathways, including TCA cycle, respiratory electron transport, oxidative stress, and metabolism pathway. Moreover, Isocitrate dehydrogenase 1(Idh1), Cytochrome P450 Family 1 Subfamily A Member 1(Cyp1a1), 3-Hydroxy-3-Methylglutaryl-CoA Synthase (Hmgcs2) and Hexokinase 2(Hk2) were identified as the hub genes and validated in the GSE5606 datasets with area under the curve(AUC)>0.7. The qRT-PCR results showed that the expression levels of Cyp1a1, Hmgcs2, HK2, and Idh1 in vitro model of DCM and controls were consistent with the bioinformatics analysis results from the mRNA microarray. Conclusions Overall,we identified hub genes and pathways involved in DCM via bioinformatics analysis and revealed the potential role of cuproptosis, providing useful and novel information to explore the potential candidate genes for DCM diagnostic and therapeutic options.